Awareness of Healthcare Faculty Students on Telehealth: A Mixed Methods Study - Aytimur, Didem; Mandıracıoğlu, Aliye; Batı, Ayşe Hilal; Gövsa, Figen (European Journal of Therapeutics, 2024)
Objective: The aim of the study is to determine the awareness and opinion of students in health professions’ faculties about telehealth. Method: This cross-sectional study was designed using a mixed methods approach including both quantitative and qualitative components. Seven hundred nighty seven second-year students from faculties of Medicine, Pharmacy, Dentistry and Nursing at Ege University were included in the study. A form including a section for personal information of the participants and items to determine students’ awareness level on telehealth was created by researchers to collect quantitative data. The qualitative data were collected through semi-structured interviews with three students from each faculty selected by purposive sampling. The relationship between responses to propositions and participants’ socio-demographic characteristics was evaluated using t-test and ANOVA. Chi-square tests were used to evaluate other characteristics of the students according to their schools and their responses to propositions about telehealth. For qualitative data, manual descriptive analysis was used. Interview transcripts were read by two researchers, code was assigned to each concept, and they were grouped under thematic headings. Results: Of the participants, 28.8% reported that they have already heard of the term telehealth. Students are much less familiar with the terms of telenursing and teledentistry. The average total awareness score of the students was 12.70±7.27 [0-27]. Conclusion: Majority of the students are found to lack sufficient awareness of telehealth. This outcome highlights importance of determining awareness levels of future healthcare professionals, who will use these services in their professional lives; especially given that telehealth services have begun to be used widely around the world and have become legally regulated in our country. It points out the necessity of receiving education on this topic during undergraduate period.